Gestational Diabetes Mellitus: Mechanisms Underlying Maternal and Fetal Complications - Jooyeop Lee; Na Keum Lee; Joon Ho Moon (Endocrinology and Metabolism)
Gestational diabetes mellitus (GDM) affects over 10% of all pregnancies, both in Korea and worldwide. GDM not only increases the risk of adverse pregnancy outcomes such as preeclampsia, preterm birth, macrosomia, neonatal hypoglycemia, and shoulder dystocia, but it also significantly increases the risk of developing postpartum type 2 diabetes mellitus and cardiovascular disease in the mother. Additionally, GDM is linked to a higher risk of childhood obesity and diabetes in offspring, as well as neurodevelopmental disorders, including autistic spectrum disorder. This review offers a comprehensive summary of clinical epidemiological studies concerning maternal and fetal complications and explores mechanistic investigations that reveal the underlying pathophysiology.